Criminal Liability Resulting In Serious Injury To The Child As The Victim (Case Study Of District Court Decision No. 000 / Pid.Sus/2022/PN.Mdn) - Fitriana, Fitriana (Universitas Dharmawangsa, 2022)
Crimes against “persons